Mimarın eğitimi üzerine spekülatif bir deneme - Yücel, Seven; Aydinli, Semra (Erciyes Üniversitesi, 2015)
“Architect’s Education” is a speculative term having double meaning connotations. Recently this term still has been used in inquiring the architectural education since its initiatives give rise to many connotations. In this article, this term consists of an interval extends from beginning of the education in the context of learning focused education strategy to the lifelong education referring to the principles of flexibility and sustainability. The debates on Architect’s Education’ also help us to inquire the mutual relationship between architecture and society from different perspectives. In Turkey the relationship between the architecture and society, the efforts in developing the politics in architecture are inadequate as the social responsibility and environmental sensibility are not developed adequately during the education. The term ‘architect’s education’ that gives way to consider all the paradoxical issues concerning architectural knowledge that requires change and resists the change, may contribute to develop the learning-focused strategies and tactics. The aim of this article is to propose a new approach to learning to learn focusing on the in- between concepts in understanding and interpreting all the deep meanings and paradoxes of education which were almost the recent themes of the debates. This research article entitled “architect’s education based on speculative experiment” tries to find out some possibilities of in-between reality that generates tactics in the context of a search for an original education strategy.

‘Mimarın eğitimi’ çift anlamlı çağrışımları olan spekülatif bir terim. Mimarlık eğitiminin sorgulanmasında bu kurgusal terimin çağrışımları farklı açılımlara neden olduğundan son yıllarda çok sık kullanılıyor. Bu makalede söz konusu terim, öğrenme odaklı eğitim stratejisi bağlamında mimar adayının eğitime başladığı ilk andan itibaren hayat boyu öğrenme sürecine uzanan bir zaman aralığını kapsıyor; ve eğitimde sürdürülebilirlik ve esneklik ilkesine gönderme yapıyor. ‘Mimarın eğitimi’ üzerine tartışmalar mimarlık toplum ilişkisini de farklı açılardan sorgulamamıza yardımcı olmakta. Türkiye’ de toplum ve mimarlık ilişkisi, mimarlık politikaları geliştirme çabaları, eğitim sırasında kazanılmayan çevresel duyarlılık ve toplumsal sorumluluk nedeniyle son derece yetersiz. Mimarlık bilgisinin değişen, değişime direnç gösteren paradoksal konularının bir arada ele alınmasına kapı açan “mimarın eğitimi” terimi öğrenme odaklı bir eğitim stratejisinin ve taktiklerin gelişmesine katkı sağlayabilir. Bu makale, günümüzde tartışmaların ekseninde yer alan eğitimin paradokslarını ve derin ilişkilerini, arada olma haline gönderme yapan araform / ara uzam kavramı üzerinden anlama ve açıklama odaklı bir yaklaşım olarak düşünülebilir. “Mimarın eğitimi üzerine spekülatif bir deneme” adlı bu araştırma yazısı özgün bir eğitim stratejisi arayışı bağlamında ara uzam gerçekliğin olası durumlarına ilişkin taktik üretme denemesi olarak düşünülebilir.
Keywords: architect’s education; lifelong learning; in-between; learning strategies; awareness; critical thinking; mimarın eğitimi; hayat boyu öğrenme; araform/ara uzam; öğrenme stratejileri; farkındalık; eleştirel düşünme